Supporting data for Cheng et al. (2018): Objective quantification of convective clustering observed during the AMIE/DYNAMO 2-day rain episodes - Cheng, Wei-Yi; Kim, Daehyun; Rowe, Angela (My University, 2018)
The data and scripts included here should enable the reproduction of the plots in Cheng et al. (2018, JGR-Atmosphere, in revision). Note that only the data required for the plots is included here.